MICROBIOLOGICAL INDICATORS OF ORAL CAVITY IN PATIENTS WITH EPILEPSY - Makhmudov M. B. (Western European Studies, 2026)
To improve the quality of dental care for patients suffering from epilepsy, a study was conducted on the impact of a general somatic disease (epilepsy) on oral microflora. It is clear that oral dysbiosis is observed in this group of patients.
Keywords: epilepsy; oral microflora; dysbiosis